Radio advertisement speech style preferences among listeners with different first languages within one country - Altrov, Rene; Pajupuu, Hille; Pajupuu, Jaan; Kiisla, Aet (Frontiers in Communication, 2023)
Objective: The goal of the study was to find out if, in a society where there is a large community of people for whom the official state language is a second language, do they prefer to listen to statelanguage radio advertisements in the same performance style as listeners for whom the official state language is their first language. Method: An experiment was conducted in Estonia, with two groups: those who spoke Estonian as their first language and those who spoke Russian as their first language and Estonian as their second. Both groups listened to Estonian-language radio advertisements presented by various spokespeople, half of which were performed in a calm style (passive arousal) and half in an energetic style (active arousal). They then rated the likability of each performance. Results: The results showed that both groups preferred the calm style but there were significant differences in the scores: the first group gave the calm style significantly higher scores than the second group, while the latter scored the energetic style more highly. Conclusion: Knowing the advertising style preferences in a society where people who have different first languages may allow for better targeting of advertising.